Leaving no one behind: Leveraging support to promote access with success in post-graduate studies - Namakula, H.; Ndaba, Mthobisi (South African Journal of Higher Education, 2024)
Postgraduate student enrolment at South African universities has increased significantly. While this is commendable, it has raised concerns about low success rates. Various scholars have identified under-preparedness, supervision challenges, mental health issues and funding, among other factors, that contribute to the post-graduate success crisis. We believe that post-graduate support services have a significant role to play in dealing with this success crisis. Therefore, in this article, we present a two-fold argument about post-graduate support in South African universities. Firstly, we argue that universities have prioritised support services aimed primarily at undergraduate students, with insufficient support at the post-graduate level, and this has negative implications for post-graduate students’ well-being, success and, ultimately, the knowledge-creating project in the South African higher education context. In so doing, we also highlight some of the gaps as potential areas of improvement in existing postgraduate support services. Secondly, we argue that improved support for postgraduate students requires well-coordinated and collaborative efforts between multiple stakeholders: supervisors, students and university support services, among others. In this way, this article contributes to the body of knowledge on access with success, illuminating the value of support in, and the intricacies of, post-graduate studies.